2018
DOI: 10.1136/bjsports-2017-098533
|View full text |Cite
|
Sign up to set email alerts
|

Sports-related injuries in New Zealand: National Insurance (Accident Compensation Corporation) claims for five sporting codes from 2012 to 2016

Abstract: Rugby union and rugby league have the highest total number and costs associated with injury. Accurate sport exposure data are needed to enable injury risk calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 26 publications
0
46
0
Order By: Relevance
“…In the same NZ hospital study, almost 1% of all cases were related to cricket injury 19. An NZ study looking at insurance claims over the 2012 to 2016 period reported 0.4% of the total claims (of the five sports investigated) were due to cricket-related injury 17. A study looking at ED presentations across Australia from 1989 to 1993 reported 3.7% of children under 15 years of age and 7.3% of all adults (defined as 15 years or older) presenting with sports injuries were cricket related 20.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In the same NZ hospital study, almost 1% of all cases were related to cricket injury 19. An NZ study looking at insurance claims over the 2012 to 2016 period reported 0.4% of the total claims (of the five sports investigated) were due to cricket-related injury 17. A study looking at ED presentations across Australia from 1989 to 1993 reported 3.7% of children under 15 years of age and 7.3% of all adults (defined as 15 years or older) presenting with sports injuries were cricket related 20.…”
Section: Resultsmentioning
confidence: 96%
“…Three studies were specific to cricket and two studies included cricket among other sports or injury reporting. Three of the studies were based in New Zealand (NZ)17–19 and two in Australia 20 21. Three studies used ED presentation data only,18 20 21 one used hospital admission data only,19 one used both ED presentation and admission data22 and one used insurance claims data 17.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rule changes made by the Amateur International Boxing Association (AIBA) in 2013 for example, resulted in a substantial decrease of boxing-related upper extremity injuries between 2012 -2016, shown most impressively in a decline of hand injuries by 33% [7,10]. Nevertheless, sports injuries still occur with high incidences, showing varying risk pro les within the different types of sport [11,12]. Injuries of the hand account for approximately 25% of all sports-related injuries [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%